If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (v + -4)(v + -7) = 0 Reorder the terms: (-4 + v)(v + -7) = 0 Reorder the terms: (-4 + v)(-7 + v) = 0 Multiply (-4 + v) * (-7 + v) (-4(-7 + v) + v(-7 + v)) = 0 ((-7 * -4 + v * -4) + v(-7 + v)) = 0 ((28 + -4v) + v(-7 + v)) = 0 (28 + -4v + (-7 * v + v * v)) = 0 (28 + -4v + (-7v + v2)) = 0 Combine like terms: -4v + -7v = -11v (28 + -11v + v2) = 0 Solving 28 + -11v + v2 = 0 Solving for variable 'v'. Factor a trinomial. (4 + -1v)(7 + -1v) = 0Subproblem 1
Set the factor '(4 + -1v)' equal to zero and attempt to solve: Simplifying 4 + -1v = 0 Solving 4 + -1v = 0 Move all terms containing v to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1v = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1v = 0 + -4 -1v = 0 + -4 Combine like terms: 0 + -4 = -4 -1v = -4 Divide each side by '-1'. v = 4 Simplifying v = 4Subproblem 2
Set the factor '(7 + -1v)' equal to zero and attempt to solve: Simplifying 7 + -1v = 0 Solving 7 + -1v = 0 Move all terms containing v to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1v = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1v = 0 + -7 -1v = 0 + -7 Combine like terms: 0 + -7 = -7 -1v = -7 Divide each side by '-1'. v = 7 Simplifying v = 7Solution
v = {4, 7}
| 64=13+3x | | 14-3(4-x)=2x | | 4p-3=17 | | (v-4)(4-7)=0 | | 4x^4+12x^2-5x+7=0 | | 10x^2-3=13x | | 3x-4=4+4x | | 10-2(2-x)=20 | | 5x-1=15x-86 | | (6x+7)-3=46 | | 2x-3+2=20 | | 9x^2-31x-20=0 | | 9-9x=48-30x | | 2v^2-19v+35=0 | | 3x+9-5=4 | | 4(-2x+5)=-2(4x+5) | | ln(x+-1)+ln(x+2)=1 | | (x+2)=3 | | 7b(-3c)= | | -3x^2-21x+24=0 | | 10+2(x+2)=2 | | 2x*6x^2= | | 3t+t=19+9 | | (x+1)-14= | | 6x*32+200= | | 9b=72 | | 5x-2=12x-44 | | 2x*12x^2= | | 6x+32-200= | | 6x+23=16x-77 | | 6(2+4)=3(3-y) | | 6(2-y)=3(3-y) |